Pemberdayaan UMKM Melalui Pemanfaatan Instagram Insight dan Branding Logo - Dwi Puspita Anggraeni (Jurnal Nusantara Berbakti, 2023)
In the digital era, some MSMEs have not been able to compete in facing the challenges of increasing visibility and turnover through digital promotion. One of the main obstacles is the limited understanding and strategies in using social media, especially Instagram, which has the potential to support market expansion and brand recognition. This Community Service activity (PKM) is designed to provide assistance to Kamala Coffee in utilizing Instagram Insight and implementing effective logo branding. The activity stages include needs analysis, preparation of training materials, hands-on training, as well as implementation and evaluation of results. Based on the results of the activities, there was a significant increase in engagement and reach of content on social media, especially through the Instagram Insight feature. The use of a new and attractive logo also helped increase brand awareness. Through this approach, Kamala Coffee is expected to maximize their digital potential to achieve their target turnover and strengthen their position in the local market.